2005
DOI: 10.7326/0003-4819-142-5-200503010-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Lifestyle Modification or Metformin in Preventing Type 2 Diabetes in Adults with Impaired Glucose Tolerance

Abstract: Background-The Diabetes Prevention Program (DPP) demonstrated that interventions can delay or prevent the development of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
490
3
29

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(526 citation statements)
references
References 37 publications
4
490
3
29
Order By: Relevance
“…The Diabetes Prevention Program demonstrated that lifestyle modification or medication is more cost effective for preventing or delaying the development of diabetes in high-risk populations with impaired glucose tolerance than are placebo treatments [8,9]. Women with a history of GDM also constitute a high-risk population.…”
Section: # 2008 Published By Elsevier Ireland Ltdmentioning
confidence: 99%
“…The Diabetes Prevention Program demonstrated that lifestyle modification or medication is more cost effective for preventing or delaying the development of diabetes in high-risk populations with impaired glucose tolerance than are placebo treatments [8,9]. Women with a history of GDM also constitute a high-risk population.…”
Section: # 2008 Published By Elsevier Ireland Ltdmentioning
confidence: 99%
“…In addition to preventing diabetes, the DPP lifestyle intervention improved several CVD risk factors, including dsylipidemia, hypertension, and inflammatory markers (29,30). The DPP analysis indicated that lifestyle intervention was cost-effective (31), but other analyses suggest that the expected costs needed to be reduced (32).…”
Section: Nutrition Recommendations and Interventionsmentioning
confidence: 99%
“…The main difference is that the models reviewed in this section assessed the progression of disease from a time prior to the onset of diabetes, when subjects would have IGT or IFG. Three of the studies assessed the long-term costs and benefits that would be expected with the use of lifestyle or pharmacological interventions for the prevention of diabetes, [171][172][173] one study considered lifestyle interventions and surgery 174 and one only assessed the impact that delaying the onset of diabetes would have 175 -without actually incorporating in the model the interventions that would be required to do this. The models used in these studies are discussed in detail below.…”
Section: Search Resultsmentioning
confidence: 99%
“…Herman and colleagues 171 reported outcomes in QALYs. The utilities associated with IGT were based on the Quality of Wellbeing Index (QWBI), which was administered to patients enrolled on the DPP trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation